Solve for y -2y-12=-8y-18

Math
-2y-12=-8y-18
Move all terms containing y to the left side of the equation.
Tap for more steps…
Add 8y to both sides of the equation.
-2y-12+8y=-18
Add -2y and 8y.
6y-12=-18
6y-12=-18
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 12 to both sides of the equation.
6y=-18+12
Add -18 and 12.
6y=-6
6y=-6
Divide each term by 6 and simplify.
Tap for more steps…
Divide each term in 6y=-6 by 6.
6y6=-66
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6y6=-66
Divide y by 1.
y=-66
y=-66
Divide -6 by 6.
y=-1
y=-1
Solve for y -2y-12=-8y-18

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top